2018
DOI: 10.21608/ejabf.2018.23926
|View full text |Cite
|
Sign up to set email alerts
|

Influence of several dietary protein and lipid levels on nutritional parameters and liver functions of Solea aegyptiaca juveniles

Abstract: Protein level Lipid level Liver enzyme activities Growth performance Digestibility coefficient A feeding trial was designed to assess the effects of dietary protein and lipid content on growth, feed utilization efficiency, and muscle proximate composition of Solea aegyptiaca juveniles. Eight diets were formulated (4 protein levels; 40, 45, 50& 55% at 2 lipid levels; 8, 12%). The results showed that growth performance in terms of weight gain, specific growth rate, condition factor, feed conversion ratio, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…So, the highest growth observed with fish fed 30% crude protein and18 kJ/g dietary energy may regarding to increasing dietary lipid content up to (14.89%) in the above diet (Table 1). The same finding was reported by Verger et al (1996) observed a protein-sparing effect by increased dietary lipid from 9 to 15% in sea bream Sparus aurata and from 4-16 in sole, Solea aegyptiaca diets ( Yones et al, 2018). The same trend was found by (Caballero et al, 1999) for Sparus aurata when fish fed with 27% dietary lipid, resulted the highest fish growth compared to fish fed diets contained 22 and 15% lipid.…”
Section: Resultssupporting
confidence: 80%
“…So, the highest growth observed with fish fed 30% crude protein and18 kJ/g dietary energy may regarding to increasing dietary lipid content up to (14.89%) in the above diet (Table 1). The same finding was reported by Verger et al (1996) observed a protein-sparing effect by increased dietary lipid from 9 to 15% in sea bream Sparus aurata and from 4-16 in sole, Solea aegyptiaca diets ( Yones et al, 2018). The same trend was found by (Caballero et al, 1999) for Sparus aurata when fish fed with 27% dietary lipid, resulted the highest fish growth compared to fish fed diets contained 22 and 15% lipid.…”
Section: Resultssupporting
confidence: 80%